Gold and Palladium Combined for the Sonogashira Coupling of Aryl and Heteroaryl Halides - Panda, Biswajit; Sarkar, Tarun K. (Synthesis, 2013)
A highly efficient gold and palladium combined methodology for the Sonogashira coupling of a wide array of electronically and structurally diverse aryl and heteroaryl halides is described. The orthogonal reactivity of the two metals shows high selectivity and extreme functional group tolerance in Sonogashira coupling. A brief mechanistic study reveals that the gold acetylide intermediate enters into the palladium catalytic cycle at the transmetalation step.
Keywords: gold catalysis; cross-coupling; Sonogashira coupling; gold–palladium combined